Performance-Based Financing Toolkit - Fritsche, GyörgyBèla (World Bank, 2015)
Performance-based financing (PBF) approaches have expanded rapidly in lower-and middle income countries, and especially in Africa. The number of countries has grown from three in 2006 to 32 in 2013. PBF schemes are flourishing and cause considerable demand for technical assistance in executing these health reforms in a rational and accountable manner.